Targeting skeletal muscle mitochondrial function with a Nrf2 activator in a novel model of musculoskeletal decline - Musci, Robert Vincent, author; Hamilton, Karyn L., advisor; Hickey, Matthew S., committee member; Lark, Daniel S., committee member; Santangelo, Kelly S., committee member (Colorado State University. Libraries, 2020)
This dissertation describes a series of three experiments with an overall objective to understand how targeting mitochondrial function with a phytochemical Nrf2 activator can prevent the onset of or mitigate the progression of mitochondrial dysfunction and sarcopenia in a novel model of musculoskeletal aging. The specific aims of the three experiments were to 1) characterize the age-related changes in skeletal muscle in Dunkin-Hartley guinea pigs; 2) assess the effect of Nrf2 activator treatment on skeletal muscle energetics by measuring mitochondrial function; and 3) determine how Nrf2 activator treatment influences components of skeletal muscle proteostasis. Dunkin-Hartley guinea pigs exhibit several characteristics reflective of human musculoskeletal aging including a decline in the proportion of type II muscle fibers, a shift towards a smaller myofiber size distribution, and a decline in muscle density in the gastrocnemius, as well as a decline in protein synthesis in both the soleus and gastrocnemius. In the second experiment, Nrf2 activator treatment improved mitochondrial respiration in both 5- and 15-month-old male and female guinea pigs. Moreover, Nrf2 activator treatment attenuated the age-related decline in mitochondrial respiration. In the third experiment, Nrf2 activator treatment attenuated the age-related decline in protein synthesis in Dunkin-Hartley guinea pigs. Altogether, these data demonstrate 1) Dunkin-Hartley guinea pigs experience age-related changes in skeletal muscle consistent with the aged musculoskeletal phenotype in humans 2) this phytochemical Nrf2 activator can improve mitochondrial function and 3) targeting mitochondrial dysfunction is an efficacious intervention to mitigate age-related declines in components of proteostasis in skeletal muscle and improve overall musculoskeletal function.
Keywords: energetics; proteostasis; aging; skeletal muscle; mitochondria